James Baldwin protest and beyond: a study of Afro-American fiction - Sharma, Asha (Rajat Publ., 2005)
James Baldwin, b. 1924, Afro-American novelist.
DK 157367
Keywords: Baldwin, James <1924-1987> -- Criticism and interpretation; Baldwin, James -- 1924-1987; Geschichte 1900-2000; American fiction -- African American authors -- 20th century -- History and criticism